2019
DOI: 10.1021/acsomega.9b00912
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Monodisperse Giant Unilamellar Anchored Vesicles Using Micropatterned Hydrogel Substrates

Abstract: Giant unilamellar vesicles (GUVs) are model membrane systems consisting of a single lipid bilayer separating an inner lumen from the outer solution, with dimensions comparable to that of eukaryotic cells. The importance of these biomimetic systems has recently grown with the development of easy and safe methods to assemble GUVs from complex biorelevant compositions. However, size and position control is still a key challenge for GUV formation and manipulation. Here, a gel-assisted formation method is introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Porous hydrogel benefits the formation of GUVs, affecting sizes and yield. [324] Schultze et al [325] prepared a micropatterned gel structure with a terpolymer, obtaining monodisperse anchored vesicles with about 10% variation in diameter. Liu et al [326] combined the gel-assisted method with extrusion by coating the gel with a microporous polycarbonate membrane, producing freestanding liposomes with an upper size limit.…”
Section: Dehydration/rehydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous hydrogel benefits the formation of GUVs, affecting sizes and yield. [324] Schultze et al [325] prepared a micropatterned gel structure with a terpolymer, obtaining monodisperse anchored vesicles with about 10% variation in diameter. Liu et al [326] combined the gel-assisted method with extrusion by coating the gel with a microporous polycarbonate membrane, producing freestanding liposomes with an upper size limit.…”
Section: Dehydration/rehydrationmentioning
confidence: 99%
“…[ 324 ] Schultze et al. [ 325 ] prepared a micropatterned gel structure with a terpolymer, obtaining monodisperse anchored vesicles with about 10% variation in diameter. Liu et al.…”
Section: Laboratory Fabrication Of Protocell Modelsmentioning
confidence: 99%
“…This procedure was found to be faster (2-60 min) than regular electro formation or delicate hydration procedure and the technique worked efficiently. [97,98,99]…”
Section: Gel Assisted Hydrationmentioning
confidence: 99%
“…Yet this method suffers from limitations such as it usually resulting in low encapsulation efficiency and producing multilamellar vesicles. This led scientists to develop other techniques such as electroformation, gel-assisted formation method or paper-assisted hydration, or microfluidics to produce vesicles in a more efficient and controllable way. Also, more recently, various hydration methods have been suggested that improve upon the simple gentle hydration techniques, including one using substrates such as polyacrylamide gel …”
Section: Approaches To De Novo Construction Of Artificial Cellsmentioning
confidence: 99%